Experimentos de campo com teto-reservatório: desempenho térmico e percepção do usuário - Fernandes, Leandro Carlos (2018)
The main objective of this research was to evaluate the potential of roof-pond for moderating the thermal environment in passive buildings face the rigors of climates with high daily temperature ranges and well defined seasons. The experiments with roof-ponds were started in Brazil in test-cells, and completed in Israel, in a test-building. The preparation of roof-pond configurations was preceded by analysis of local climates for the definition of design guidelines. In Brazil, in test-cells, roof-ponds were oriented to solar heating, evaporative cooling and reduction of daily temperature ranges. Monitoring was conducted to evaluate thermal performance for more than two years, from the second half of 2014 until the first of 2017. The monitoring took place in the city of Curitiba, with humid subtropical climate. In Israel, in the test-building, roof-ponds were oriented towards cooling. Experiments on thermal performance and thermal perception were carried out from June to September 2017. The experiments took place at the Sde-Boqer Campus, Ben-Gurion University of the Negev, place with a predominantly arid climate. Experiments on thermal perception began in July and ended in September, with the participation of 53 volunteers. For the analysis of the results concerning the thermal performance of the test-cells and the test-building, specific indices and a method for estimating internal hourly temperatures were developed. In addition to the indices created, hourly temperatures, mean temperatures and the decremental factor were also used. To analyze the results of the study on thermal perception, statistical analysis and comparison of estimated responses (PMV and PPD) with reported responses were used. From the results of the studies on thermal performance, it was concluded that the roof-pond has a high potential for moderation of the rigors of the analyzed external climates, allowing the reduction of daily thermal amplitudes (in light buildings) and the heating and structural cooling of the building. The results of the study on thermal perception indicated that the volunteers considered the roof-pond conditioned environment more comfortable than the air conditioning unit. There was greater agreement with the EN-15.251 and ISO 7730 (PMV) models than with the ANSI / ASHRAE Standard 55 model and the bioclimatic chart used. Apparently, users would tolerate temperatures slightly above the limits proposed by the bioclimatic chart.